1988
DOI: 10.1007/bf01417870
|View full text |Cite
|
Sign up to set email alerts
|

The structure of water and methanol adsorbed on silica gel by FT-NIR spectroscopy

Abstract: The NIR adsorption spectra were analyzed quantitatively on the fundamental, combination and first overtone region of OH vibrations of silanol groups, water and methanol adsorbed on mesoporous silica gels. Adsorbed methanol constitutes first layer of about 3 molecules/ran -2 and second layer, the structure of which is similar to that of bulk methanolliquid. Adsorbed water consists of a first layer of about 3 molecules/nrn-2, the second layer of about 9 molecules/nm -2 and the third layer has a structure similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 13 publications
3
21
0
1
Order By: Relevance
“…In number of molecules this translates into 3 water molecules to 2 silanol groups. This result agrees with that of Yamauchi and Kondo [13].…”
Section: Spectral Region 5400-5100 CM -1supporting
confidence: 93%
See 1 more Smart Citation
“…In number of molecules this translates into 3 water molecules to 2 silanol groups. This result agrees with that of Yamauchi and Kondo [13].…”
Section: Spectral Region 5400-5100 CM -1supporting
confidence: 93%
“…Since the natures of the hydroxyl groups on the silica gel surface are different, the environments of the adsorbed water molecules on the surface are also different. The state of the water molecules on silica gel particles and related substances have been studied by using several different techniques including TGA [2], NMR [3,4], IR and NIR [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], AB initio calculations [20] and dielectric measurements [21]. Most of these studies were trying to give a picture of the water structure on silica surface based on the results from the respective analytical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, additional water molecules adsorb rather to the adsorbed water molecules than to free hydroxyls, which are energetically less favorable. Also Yamauchi and Hondo [42] examinating water adsorption to silica gel found that water would adsorb only to a part of the hydroxyl groups, as SiOH-OH 2 complex and the additional water would 'settle' on the previous 'silanol water'. The adsorption of water on a fully hydroxylated surface of β(α)-cristobalite covered by the geminal hydroxyl groups was also studied by Yang and co-workers [43] using density-functional total-energy and molecular dynamics calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Another possibility is to study the near infrared region, where the combination modes v~(H20) + g(HzO) and v(OI-I) + 8(HO) absorb (5500 to 4000 cm J). In this region, the H20 should exhibit a band between 5300 and 5180 cm-t, and the hydroxyl group in the neighborhood of 4 5 0 0 -4000 cm -t (Yamamuchi and Kondo 1988). Figure 7 shows the spectra of vermiculite ( Figure 7A) and dry NH4CI ( Figure 7B) in the NIR region.…”
Section: The Presence Of Molecular Water In Ammonium Ver-miculite Andmentioning
confidence: 98%
“…The analysis will be based on: 1) the generally accepted rule that hydrogen bonding will depress the stretching frequency of NH4 + and will increase the frequency of its bending mode (Cotton and Wilkinson 1988;Yamamuchi and Kondo 1988); 2) the comparison of the spectrum of ammonium in vermiculite with the spectra of NH4 + in environments for which there is some knowledge about its hydrogen bonding properties. In this paper we will evaluate the hydrogen bonding properties of NH4 + in vermiculite in relation with the ones of NH4 + in I-, CI-, and Brlattices, as well as in H20 solution.…”
Section: H-bonding Properties Of Nh4 + Ions In Vermiculitementioning
confidence: 99%